Pengaruh Price Discount, Store Atmosphere, dan Display Product terhadap Impulse Buying pada Matahari Department Store - Siskawati .; Budi Prabowo (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aimed to determine the effect of Price Discount, Store Atmosphere, and Product Display on Impulse Buying at Matahari Department Store. This research uses quantitative methods. The population in this study were consumers of Matahari Department Store Royal Plaza Surabaya with a sampling technique that is purposive sampling. The number of samples used in this study was 100 respondents with a questionnaire data collection technique. The data analysis technique used to answer the proposed hypothesis is multiple linear regression using SPSS 25 For Windows. The results of this study indicate that: (1) Price Discount, Store Atmosphere, and Product Display simultaneously influence Impulse Buying for consumers at Matahari Department Store Royal Plaza Surabaya. (2) Price Discounts partially affect Impulse Buying for consumers at Matahari Department Store Royal Plaza Surabaya. (3) Store Atmosphere partially influences Impulse Buying for consumers at Matahari Department Store Royal Plaza Surabaya. (4) Product display partially does not affect consumer impulse buying at Matahari Department Store Royal Plaza Surabaya. Keywords: Price Discounts; Store Atmosphere; Product Display; Impulse Buying